Study of the temporary space characteristics in the main stage of the fast throwing in a Baseball game - Ahmed Pilotos-Martínez; Alina María Morejón-Díaz; Yanelbys Miranda-Camejo (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2012)
The improvement of athletes throughout history, has been influenced by multiple factors among those are the genetics, the feeding, and the physical controls. At present, one of these factors is the improvement of the technique performance, under scientifically planned trainings that have been a result of biomechanical studies of high technology. The biomechanical study of the sport techniques practices based on the cinematic study of videos, is the main method that scientists use to offer information to trainers and athletes about the behavior of the cinematic characteristics determining the sport improvement. For that reason this research has as objective: To study the behavior of the temporary space characteristics in the fast throwing using the software HU-M-AN. The measuring and the observation were the empiric and biomechanical methods that we used together with the theoretical methods such as analysis - synthesis, deductive - inductive, to detect the behavior of the temporary space characteristics in the pitcher study object. These methods allowed to carry out a much more precise study that the one used by the trainer, who generally does it starting from the direct observation when their athletes execute the technique. This procedure allowed to offer the trainer information about the mistakes showed in the performance of the fast throwing, contributing to the study of the technical performance so that make more efficient the technical preparation of pitchers, because it deals with an skilled athlete and in this way it is kept the quality that has characterized the pitchers of Pinar del Río province.